(untitled) (Homoeopathy for All, 2024)
Sleep is a natural and essential state of rest for the body and mind. It is characterized by reduced consciousness, decreased sensory activity, and limited movement. Sleep plays a crucial role in several aspects of our lives. During sleep, the body repairs and rejuvenates tissues, muscles, and organs. It’s a time for the body to recover from daily wear and tear. Quality sleep supports the immune system, helping the body defend against illnesses and infections. Adequate sleep is linked to better emotional regulation, mental well-being, and overall quality of life.